(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study began with the results of observations that had been carried out at the Pasir Indah Village Women’s Volleyball Court. It was found that there were still many players who did not have good upper service skills; most players performed upper services with the wrong technique. This study aims to determine the Effect of Dumbbell Weight Training on the Upper Service Ability of the Pasir Indah Village Women’s Volleyball Club. This study was conducted using a quasi-experimental method with a One-Group Pretest-Posttest Design. The population in this study were 16 Pasir Indah Village Women’s Volleyball Players, while the sampling technique used was saturated sampling, where all populations were sampled. The research design used a Pre-Test and Post-Test. The instrument used was an upper service ability test. Data analysis and testing of research hypotheses used the independent t-test (t-test) analysis technique with a significance level of α = 0.05. The test results showed that there was an Effect of Dumbbell Weight Training on Upper Service Ability. The hypothesis test shows a value (t count 15.025 > t table 1.753), so that it shows that Ho is rejected and Ha is accepted, which means that there is a significant influence on increasing the ability of upper service after being treated with the Dumbbell Weight Training Method.